Medical ethics education - Piryani, R M (Journal of Chitwan Medical College, 2015)
Ethics education is essential for everyone but indispensable for health care professionals. Health care professionals must strive for excellence as much as possible. The moral duty of health care professionals is to do the best for their patients and take healthcare decision based on evidence and clinical, technical and ethical ground. However, most of the times ethical aspects are either ignored, undermined or overlooked. There seems to be some gap in teaching and learning and its application in practice. The fundamental idea to teach medical ethics at undergraduate level is to sow the seeds to ethics at an early stage in the minds of health care professionals to deliver excellent health care to the community. All religions prescribe ethical and moral behaviour and thought for their followers. Hinduism through Bhagwat Gita preaches karma as the only dharma, Islam speaks of Khuluq, Buddhism of the 10 meritorious deeds, Jainism of three ratnas, Christianity of service and stewardship. Let’s invest our efforts in enhancing medical ethics education in our institutions besides technical education and produce quality healthcare professionals who can take healthcare decision based on evidence, and clinical, technical and ethical ground. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12557